People participating in the 1986 y-Walk - Unknown:::Creator::::::::::::
Negative shows men and women participating in the 1986 y-Walk. They are walking in a crosswalk. Some of the participants are wearing tee shirts that read: "Walk for women. YWCA 1986" and some are carrying balloons. There is a wooden covered sidewalk in the background.